Exoplanets : finding, exploring, and understanding alien worlds - Kitchin, Chris (Astronomers' Universe, 2012)
Since 1992 there has been an explosion in the discovery of planets orbiting stars other than the Sun. There are now around 600 alien planets that we know about and that number is likely to break through the 1,000 'barrier' within a couple of years. The recent launch of the Kepler space telescope specifically to look for new worlds opens the prospect of hundreds, maybe thousands, of further exoplanets being found. Many of these planets orbits stars that are not too different from the Sun, but they are so close in to their stars that their surfaces could be flooded with seas of molten lead - or even molten iron. Others orbit so far from their stars that they might as well be alone in interstellar space. A planet closely similar to the Earth has yet to be detected, but that (to us) epoch-making discovery is just a matter of time. Could these alien worlds could provide alternative homes for humankind, new supplies of mineral resources and might they might already be homes to alien life? Exoplanets: Finding, Exploring, and Understanding Alien Worlds takes a look at these questions - examining what such planets are like, where they are, how we find them and whether we might ever be able to visit them. It is written for the non-specialist but also provides a comprehensive, accurate and balanced summary useful to researchers in the subject. Above all this book explores the excitement of how a new branch of science is born, develops and in less than two decades starts to become a mature part of our knowledge of the universe.